Particulate Matter Containing Environmentally Persistent Free Radicals and Adverse Infant Respiratory Health Effects: A Review. Issue 1 (20th December 2012) - Saravia, Jordy; Lee, Greg I.; Lomnicki, Slawo; Dellinger, Barry; Cormier, Stephania A.
ABSTRACT The health impacts of airborne particulate matter (PM) are of global concern, and the direct implications to the development/exacerbation of lung disease are immediately obvious. Most studies to date have sought to understand mechanisms associated with PM exposure in adults/adult animal models; however, infants are also at significant risk for exposure. Infants are affected differently than adults due to drastic immaturities, both physiologically and immunologically, and it is becoming apparent that they represent a critically understudied population. Highlighting our work funded by the ONES award, in this review we argue the understated importance of utilizing infant models to truly understand the etiology of PM‐induced predisposition to severe, persistent lung disease. We also touch upon various mechanisms of PM‐mediated respiratory damage, with a focus on the emerging importance of environmentally persistent free radicals (EPFRs) ubiquitously present in combustion‐derived PM. In conclusion, we briefly comment on strengths/challenges facing current PM research, while giving perspective on how we may address these challenges in the future. © 2012 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:56‐68, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21465